Tai Chi Chuan Exercise for Patients with Cardiovascular Disease. (17th November 2013) - Lan, Ching; Chen, Ssu-Yuan; Wong, May-Kuen; Lai, Jin Shin
Abstract : Exercise training is the cornerstone of rehabilitation for patients with cardiovascular disease (CVD). Although high-intensity exercise has significant cardiovascular benefits, light-to-moderate intensity aerobic exercise also offers health benefits. With lower-intensity workouts, patients may be able to exercise for longer periods of time and increase the acceptance of exercise, particularly in unfit and elderly patients. Tai Chi Chuan (Tai Chi) is a traditional Chinese mind-body exercise. The exercise intensity of Tai Chi is light to moderate, depending on its training style, posture, and duration. Previous research has shown that Tai Chi enhances aerobic capacity, muscular strength, balance, and psychological well-being. Additionally, Tai Chi training has significant benefits for common cardiovascular risk factors, such as hypertension, diabetes mellitus, dyslipidemia, poor exercise capacity, endothelial dysfunction, and depression. Tai Chi is safe and effective in patients with acute myocardial infarction (AMI), coronary artery bypass grafting (CABG) surgery, congestive heart failure (HF), and stroke. In conclusion, Tai Chi has significant benefits to patients with cardiovascular disease, and it may be prescribed as an alternative exercise program for selected patients with CVD.